Asymmetric Hydrogenation of 2‐Aryl‐5, 6‐dihydropyrazine Derivatives with Chiral Cationic Ruthenium Diamine Catalysts. Issue 10 (29th September 2014) - Li, Yong; He, Yanmei; Chen, Fei; Fan, Qinghua
Abstract The first asymmetric hydrogenation of unfunctionalized 2‐substituted and 2, 3‐disubstituted 5, 6‐dihydropyrazines catalyzed by chiral cationic Ru‐diamine complex (R, R)‐1a was developed, affording chiral piperazine derivatives with good enantioselectivities (up to 89% ee).